Review of Emission Inventory in Korea and Direction for Improvement 국내 대기오염 배출자료의 평가와 발전 방향 - Jang, Young Kee; Kim, Soon Tae; Woo, Jung Hun (Journal of Korean Society for Atmospheric Environment, 2023)
In this study, we focused on the Clean Air Policy Support System (CAPSS), which provides current national air pollution emission data, and compared and analyzed domestic and international emission estimation methods and uncertainty assessment methods. We evaluated the level of domestic emissions using modeling and observational data and proposed strategies to improve national air pollution emission data. Comparing the uncertainty of Korea’s CAPSS inventory with other Asian countries’ inventories, it showed a lower level of uncertainty compared to TRACE-P’s China level but similar to Japan’s emission uncertainty level. Recent studies on CAPSS inventory data uncertainty indicated relatively higher uncertainty in agricultural emissions (manure management), organic solvent use (paint facilities), fine dust emissions (fugitive road dust), and on-road mobile sources (passenger cars and trucks). Based on long-term simulation results, we examined overall emission characteristics. For air pollutants like PM10 that were underestimated, it was determined that improvements were needed, taking into account unaccounted emission sources, emission factors, and activity data on a regional basis. In the case of PM2.5, simulation accuracy was higher compared to PM10, but improvements were needed for overestimated or underestimated components. Regarding NO2, annual average concentrations were similar to observational data, but seasonal variations showed some differences, indicating uncertainties in the process of allocating monthly emissions from annual averages. Evaluation of volatile organic compounds (VOCs) revealed significant underestimation in industrial areas such as Yeosu, unlike urban areas, suggesting the need for improvements in fugitive emissions and VOC emission data related to industrial processes. To enhance the reliability of national air pollution emission data, a comprehensive understanding of industrial emissions and investigation and improvement of unreported emission sources are urgently required at the national level. Moreover, enhancing statistical data on emission-related activities should be pursued at the government level.
Keywords: Air pollutant; CAPSS; Emissions inventory; Evaluation; Uncertainty